تحليل معوقات تعلم اللغة العربية لدى الطلاب الصف الثاني المتوسط بمدرسة الدّرّة ميدان - Cut Mawaddah Al Mukarramah, Cut; Sinaga, Sopian; Sapii, Muhammad (Cahaya Ilmu Bangsa Institute, 2025)
The formulation of the problem of this study is, 1) What are the obstacles faced in understanding Arabic language learning? 2) And how to overcome the obstacles faced by students in learning Arabic? This study is a qualitative study with a descriptive approach with a qualitative descriptive method. The results of this study are: 1) Obstacles when learning Arabic experienced by students, namely: a) every student who comes to SMP IT Ad Duraah comes from a different background. b) does not have a great interest in learning Arabic. c) lack of attention to students in learning Arabic. d) lack of motivation in themselves. e) there is a problem of comprehension (intelligence) in students. f) there is no preparation for students in learning Arabic. g) Lack of respect from students for the learning teacher and also their Arabic language lessons. Because it is too monotonous when the lesson begins. 2) The method of overcoming these problems is: a) before the lesson begins the teacher always motivates students. b) before the lesson the teacher tells stories about positive and interesting things. c) the teacher makes games in Arabic lessons, to increase the enthusiasm for learning. d) gives prizes to students who are able to answer questions from the teacher. e) the teacher makes interesting media to attract students' attention.